Now & Forever - Connealy, Mary (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"In the late 1860s, homesteader Shannon Wilde tumbles over a cliff with mountain man Matthew Tucker, and their adventures begin. Can they survive as they learn to love and protect each other--for better or worse?"--
Keywords: Sheep ranchers -- Fiction; Man-woman relationships -- Fiction; Frontier and pioneer life -- Fiction; Western stories; Love stories; Christian fiction